2014
DOI: 10.2478/agms-2014-0013
|View full text |Cite
|
Sign up to set email alerts
|

Heisenberg Hausdorff Dimensionof Besicovitch Sets

Abstract: We consider (bounded) Besicovitch sets in the Heisenberg group and prove that L p estimates for the Kakeya maximal function imply lower bounds for their Heisenberg Hausdorff dimension.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Remark 14.5. In [21] in the Heisenberg group we found the same lower bound n+4 2 for the Hausdorff dimension of bounded Kakeya sets when n ≤ 8. Moreover, we derived a better lower bound 4n+10 7 for n ≥ 9 from the Kakeya estimate obtained by Katz and Tao ( [14]) using arithmetic methods (see also Remark 12.1).…”
Section: Moreover By (122)supporting
confidence: 61%
See 3 more Smart Citations
“…Remark 14.5. In [21] in the Heisenberg group we found the same lower bound n+4 2 for the Hausdorff dimension of bounded Kakeya sets when n ≤ 8. Moreover, we derived a better lower bound 4n+10 7 for n ≥ 9 from the Kakeya estimate obtained by Katz and Tao ( [14]) using arithmetic methods (see also Remark 12.1).…”
Section: Moreover By (122)supporting
confidence: 61%
“…Note that in the proof of Lemma 14.8 we showed that Axiom 2 holds also with balls defined with respect to d ∞ and tubes defined with respect to the Euclidean metric in the case of a Carnot group of step 2 and m 2 = 1 (see ( 123)). Thus we could prove the following, which for Heisenberg groups is the same as Theorem 1 in [21] (and it can be proved as Theorem 4.1). Let G be a Carnot group of step 2 with m 2 = 1, let 1 ≤ p < n, β > 0 such that n + 1 − βp > 0.…”
Section: Axiommentioning
confidence: 80%
See 2 more Smart Citations
“…The Heisenberg Hausdorff dimension of Euclidean Kakeya sets has been studied in [16] where the author showed a lower bound on the dimension of Kakeya sets. In [17], the author studied Kakeya sets for general metric spaces in axiomatic sense.…”
Section: Definition 11mentioning
confidence: 99%